THE EFFECT OF PERSONAL BUDGETING AND FINANCIAL LITERACY ON GEN Z INVESTMENT DECISIONS - Cahyani, Kadek Sintia Dwi; Meidyna, Ida Ayu Nabila; Antara, Dewa Made Dwi Juni (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study was conducted with the aim of examining the effect of personal budgeting and financial literacy on Generation Z's investment decisions in Bali Province. After the COVID-19 pandemic, Generation Z began to actively engage in digital investments as part of their financial adaptation and economic recovery. This phenomenon highlights the importance of understanding the behavioral and cognitive factors that influence their financial decision-making. This research is unique in terms of the combination of variables tested—particularly personal budgeting—which is still rarely studied together with investment decision-making, especially in the context of Generation Z. The study adopts a quantitative approach, utilizing a questionnaire with Likert scale measurements. The sampling method applies the Slovin formula with a 10% margin of error, yielding 100 respondents from a total Generation Z population in Bali of 1,127,520 individuals. These results suggest that better financial planning and knowledge contribute to more rational and responsible investment behavior. In addition, this study contributes to the achievement of the Sustainable Development Goals (SDGs), specifically Goal 4 (Quality Education), through the promotion of financial literacy as a 21st-century life skill, and Goal 8 (Decent Work and Economic Growth), by empowering youth with financial competencies that support inclusive economic growth. The insights provided can serve as a reference for educational institutions, policymakers, and financial service providers in designing strategies to enhance financial capabilities among the younger generation.